Performance of Fiber normal – weight concrete Exposed to Elevated Temperatures - nan, nan (Iraqi Journal of Civil Engineering, 2012)
The main rule of this search is determining the effect adding various types of fiber to normal concrete mixes on performance normal strength concrete ,it has been used three types of fibers (glass, short steel fibers& long steel fibers)with different contents in mixes(0.5,1.0&1.5%) respectively. It had been cast (210) cubes with dimensions (100×100×100m) mm,(160) cylinders with dimensions (100×200) mm , All concrete specimens heated under different temperatures (100,200,300,400,500 &600 C°) at age 28 days, so that it had been stayed under specified temperatures about two hours then , cooled in naturally in room temperatures and tested in compressive for cubes &splitting strength for cylinders. The results stated that the fiber improve the compressive strength under fire temperatures about (87%) compare with reference mixes, and the fiber glass take little differences than steel fiber in splitting strength when its content reach (1.0,1.5%) respectively and using this types of fibers improved the properties of concrete against the fire.